Formulation of flour fortified with freeze-dried malunggay (moringa oleifera) seeds: Evaluation of the functional and physicochemical properties - Ngo, Karen G (Animo Repository, 2024)
Malunggay (Moringa oleifera) is a versatile plant having a wide array of medicinal properties due to the presence of bioactive compounds. It has been explored as a source of nutrients in food fortification programs. Flour, which is a staple ingredient in human diet, has been used as an effective matrix in multimicronutrient fortification to address the demand for nutrient-enriched foods. However, the utilization of Malunggay seeds as a flour material has not been explored, hence this study. This study explored the possibility of preparing flour from Malunggay seeds and integrating it into wheat flour to improve its nutritional value. The screening of the Malunggay/wheat flour blends was done to assess its physicochemical and functional properties. The SEM analysis revealed that cooking the flour blends made the morphology amorphous and compact in contrast to the loose packing of the raw flour blends. Moreover, FTIR analysis validated the different proximate composition of the flour samples. Among the flour blends, MF10 exhibited significant differences in the functional property test results and gelatinization and retrogradation experiments. Nevertheless, it is recommended that further analyses, such as intro digestibility and solid-state NMR should be conducted in order to further investigate the interaction that occurs when the flour samples are subjected to higher temperature conditions. Baking tests, cooking applications, and sensory evaluation may also be performed to evaluate the applicability of the flour for food formulations.